Estimation of Potential Outage Risk Evaluation of System using Performance Indices - B. G., Manjula; Raghavendra, G. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Primary concern of power system is economical operation, but an equally defensive factor is the desire to maintain security. It is imperative to study the state of system by outage analysis and monitor its impact in advance to minimize the occurrence of cascaded disruptions. In power flow analysis the possibility of any error in measurement is not considered assuming all values as accurate. Due consideration is taken to minimize these errors adopting weighted Least square state estimation method incorporating synchronized PMU measurements. Overall severity index is the guideline selected in evaluating the stress on IEEE 5 and IEEE 14 bus systems. Highest indexed events are ranked on the top indicating too troublesome conditions leading the system towards risk.